Comprensión de textos escritos en estudiantes de primero y segundo grado de secundaria en instituciones educativas de Nauta 2021, según tipo de gestión - Guevara Rivas, Xuxa Miluska (2022)
The objective of this study was to compare first and second year students’ reading comprehension skills at secondary private and public schools in Nauta city. The study type was comparative with field study, contemporary transectional, and univariate designs. The study population was made up by 444 first year students and 429 second year students with a probabilistic sample with proportional affixation of 206 and 203 respectively. The data gathering tool was a valid and reliable reading comprehension test. Results show that private school students outperformed the state school students as their mean score was higher (14,598 > 11,749), achieving the expected level of performance whilst the state students are in process. The same was for the second year students (13,37 > 12,796); however, both groups are in process. In conclusion, the non parametric Mann-Whitney’s U test show that there is statistically significant difference between first year students (p-value = 0,000 < ? = 0,05). However, for second year students, there is no significant difference between private and state school students, as p-value = 0,099 > ? = 0,05.